2008
DOI: 10.1189/jlb.0907656
|View full text |Cite
|
Sign up to set email alerts
|

Cellular trafficking of lipoteichoic acid and Toll-like receptor 2 in relation to signaling; role of CD14 and CD36

Abstract: Lipoteichoic acid (LTA) is a central inducer of inflammatory responses caused by Gram-positive bacteria, such as Staphylococcus aureus, via activation of TLR2. Localization of TLR2 in relation to its coreceptors may be important for function. This study explores the signaling, uptake, and trafficking pattern of LTA in relation to expression of TLR2 and its coreceptors CD36 and CD14 in human monocytes. We found TLR2 expressed in early endosomes, late endosomes/lysosomes, and in Rab-11-positive compartments but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 71 publications
6
119
1
4
Order By: Relevance
“…To determine whether these surface molecules are important for cytokine response to LTA by primary microvascular endothelial cells, HDMEC were pre-incubated with blocking antibodies to CD14 and CD36 (n 5 3). FA6-152 is a mAb that recognizes amino acids 155-185, the immunodominant domain, of CD36, and has been shown to inhibit LTA binding and cytokine production by human monocytes [23]. We found that the IL-6 response was reduced by 60% by anti-CD14, but anti-CD36 had no effect (Fig.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…To determine whether these surface molecules are important for cytokine response to LTA by primary microvascular endothelial cells, HDMEC were pre-incubated with blocking antibodies to CD14 and CD36 (n 5 3). FA6-152 is a mAb that recognizes amino acids 155-185, the immunodominant domain, of CD36, and has been shown to inhibit LTA binding and cytokine production by human monocytes [23]. We found that the IL-6 response was reduced by 60% by anti-CD14, but anti-CD36 had no effect (Fig.…”
mentioning
confidence: 69%
“…In addition to further increases in TLR2, CD14 and CXCL10 transcripts (6.171.4-, 14.874.8-and 3.971.5-fold, respectively) compared to treatment with IFN-g alone, there was significant upregulation of a number of inflammatory genes including the chemokines CCL2 and IL-8 (6.372.1-and 28.2719.3-fold, respectively), cytokines To further define the interaction between LTA and TLR2 on primary human endothelial cells, the role of co-receptors was examined. The requirement of CD36 and CD14 for murine macrophages and human monocytes in response to LTA in vitro is well documented [3,8,22,23]. The scavenger molecule CD36, in particular, is deemed to be critical in vivo as CD36-deficient mice suffer significantly higher mortality from a systemic S. aureus infection compared to WT mice [3,22].…”
Section: Ifn-c Priming Of Hdmecmentioning
confidence: 99%
“…The same group demonstrated that TLR2 and MyD88 colocalize to the phagosomal vacuole of RAW macrophages infected with a live vaccine Ft strain (14). TLR2 also can become available for signaling from within endosomal vacuoles in human monocytes stimulated with internalized staphylococcal lipoteichoic acid (56). O'Connell et al (57) demonstrated that intracellular TLR2 was responsible for the initiation of signal transduction events by Chlamydia trachomatis.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have now demonstrated that TLR2 is recruited to the phagosome, where it becomes available for signaling (14,(55)(56)(57). Structurally, this model is not at all unanticipated, given that the phagosomal membrane is initially derived from the plasma membrane (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 and TLR2, in cooperation with the CD14 receptor, recognize Gram-negative or Gram-positive pathogens, respectively. Lipoteichoic acid, which represents the major component of the Gram-positive bacterial cell wall, stimulates mammalian phagocytes by activating the TLR2, CD14, and CD36 receptors (Lotz et al 2004;Nilsen et al 2008). LPS activates phagocytes that explore components of the TLR4/CD14/MD2 complex as well as a few other proteins and receptors (Leon et al 2008).…”
Section: Introductionmentioning
confidence: 99%